2011
DOI: 10.1210/jc.2010-2255
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Soy Phytoestrogen Supplementation on Thyroid Status and Cardiovascular Risk Markers in Patients with Subclinical Hypothyroidism: A Randomized, Double-Blind, Crossover Study

Abstract: There is a 3-fold increased risk of developing overt hypothyroidism with dietary supplementation of 16 mg soy phytoestrogens with subclinical hypothyroidism. However, 16-mg soy phytoestrogen supplementation significantly reduces the insulin resistance, hsCRP, and blood pressure in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
1
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(85 citation statements)
references
References 54 publications
3
78
1
3
Order By: Relevance
“…Soy protein has been studied and may interfere with levothyroxine absorption. Sathyapalan et al(572) performed a doubleblind crossover study and demonstrated that there was an increased risk of developing OH in patients who originally had SCH, when they received a vegetarian diet (containing 30 g soy protein and 16 mg phytoestrogen) as compared to a Western diet (containing 30 g soy protein and 2 mg phytoestrogens).The use of various thyroid hormone analogs that can be purchased over the internet to enhance thyroid function is a very controversial area. TRIAC is a naturally occurring metabolite of L-T4 that has significant metabolic action.…”
mentioning
confidence: 99%
“…Soy protein has been studied and may interfere with levothyroxine absorption. Sathyapalan et al(572) performed a doubleblind crossover study and demonstrated that there was an increased risk of developing OH in patients who originally had SCH, when they received a vegetarian diet (containing 30 g soy protein and 16 mg phytoestrogen) as compared to a Western diet (containing 30 g soy protein and 2 mg phytoestrogens).The use of various thyroid hormone analogs that can be purchased over the internet to enhance thyroid function is a very controversial area. TRIAC is a naturally occurring metabolite of L-T4 that has significant metabolic action.…”
mentioning
confidence: 99%
“…A recent study of administration of soy phytoestrogen in 2 different doses to individuals with subclinical hypothyroidism found that 10% of the 60 subjects progressed to overt hypothyroidism while receiving 16 mg/day over 8 weeks. 9 This dose was selected to duplicate the amount of phytoestrogen in a vegetarian diet.…”
Section: Discussionmentioning
confidence: 99%
“…Subgroup analyses showed that isoflavones significantly lowered CRP by 0.70 mg/L ( p = 0.003) among women with baseline CRP concentrations greater than 2.2 mg/L, which was equivalent to an approximate 22% reduction in levels of this inflammatory marker, whereas no change was noted in women with lower baseline CRP levels [164]. Subsequently published research also reported decreases in CRP in response to various soy interventions (soy protein, soyfoods or isoflavones) including studies involving participants engaged in an exercise program [165], subclinical hypothyroid patients [166], diabetic patients [167,168], patients with liver disease [169] and patients with renal disease [169,170]. Conversely however, soy was without effect in several other studies [120,160,171,172,173,174,175,176].…”
Section: Effects Of Soy Protein On Cardiovascular Disease Risk Facmentioning
confidence: 99%
“…However, clinical research published in 2012 indicates that the iodination of isoflavones is negligible and clinically irrelevant [425]. One small British study did find that modest isoflavone exposure (16 mg/day) increased the likelihood of progressing from subclinical to overt hypothyroidism [166]. These results are surprising because the progression of subclinical to overt hypothyroidism among Japanese patients is not elevated [426] nor are rates of hypothyroidism elevated in Japan [427].…”
Section: Thyroid Functionmentioning
confidence: 99%